Systematic Experimental Investigations and Modeling of the Heat Transfer in Additively Manufactured Periodic Open Cellular Structures with Diamond Unit Cell - Littwin, Giulia; Röder, Susanne; Freund, Hannsjörg (Industrial & Engineering Chemistry Research, 2021)
Additively manufactured periodic open cellular structures (POCS) represent a new class of structured catalyst carriers due to their favorable characteristics such as high specific surface area, low pressure drop, and remarkable heat transport properties. The periodic, well-defined, and reproducible geometry makes systematic investigations and geometric optimization possible. For a detailed optimization, models for the description of the transport characteristics of POCS are necessary. Besides the geometric parameters of the unit cell, the unit-cell geometry itself has a major effect on the dispersive thermal conductivity. POCS based on the diamond unit cell show a superior dynamic thermal conductivity in comparison to cubic structures and are therefore examined in detail. From the measurement results and the corresponding model parameters, influences of the geometric parameters of the structures are found. This leads to new design correlations for the heat transport in POCS. With this, a model-based optimization of POCS for a specific application, such as strongly exothermic reactions, is possible.
CRIS-Team Scopus Importer:2021-05-14